Flexible transparent electrode with light conversion function and preparation method and application thereof
By introducing a light conversion layer into the transparent electrode, the problem of the single function of the existing transparent electrode is solved, the photoelectric conversion efficiency and stability are improved, and the spectral conversion capability is enhanced, making it suitable for flexible optoelectronic devices such as solar cells and light-emitting diodes.
Patent Information
- Application Number
- CN202511264864.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-12-23
AI Technical Summary
Existing transparent electrodes in optoelectronic devices only have a single charge transport function, and silver nanowire electrodes are easily oxidized and migrated in air, affecting their long-term stability and photoelectric conversion efficiency. Existing spectral conversion materials are complex to introduce into battery structures and are difficult to mass-produce.
A flexible transparent electrode was prepared by using cesium tribromoleadate quantum dots and polymethyl methacrylate to form a light conversion layer, combined with a silver nanowire layer, a flexible substrate layer and an encapsulation layer, and then spin-coating and heat treatment to impart spectral conversion capability to the electrode and protect the silver nanowires.
Without altering the original device structure, the photoelectric conversion efficiency was improved, the utilization rate of ultraviolet-blue light was enhanced, and the stability of the silver nanowire electrode was increased. The fabrication process is simple and low-cost.
Smart Images

Figure CN121194544A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new materials technology, and in particular relates to a flexible transparent electrode with light conversion function, its preparation method and application. Background Technology
[0002] Solar energy is one of the most promising environmentally friendly energy sources, with a radiation level on the Earth's surface reaching 1.8 × 10⁻⁶. 14 Kilowatts. Solar cells can directly convert solar energy into electricity, providing a clean and sustainable solution to the world's ever-growing energy demand. However, the spectral response of current solar cells in the ultraviolet-blue light band is generally poor, limiting further improvements in their photoelectric conversion efficiency (PCE). By using spectral conversion technology to convert high-energy photons with weak cell response into visible-near-infrared photons that can be efficiently absorbed, the PCE of commercial solar cells can be effectively improved.
[0003] Currently, existing technologies typically introduce spectral conversion materials into the transport layer or photoactive layer of the battery structure. While this improves the system's utilization of the solar spectrum to some extent, it also brings problems such as high process complexity, the need to redesign the battery structure, and poor compatibility with existing production lines, hindering large-scale production and practical application. On the other hand, silver nanowire-based flexible transparent electrodes are becoming highly competitive electrode materials for next-generation flexible optoelectronic devices due to their excellent conductivity, light transmittance, mechanical flexibility, and low material cost. However, these electrodes have a relatively single function, mainly undertaking charge transport and lacking spectral conversion capabilities, thus failing to further improve the device's ultimate efficiency. Furthermore, the easy oxidation and migration of silver nanowires in air severely affects their long-term stability, restricting their application in high-efficiency and stable solar cells.
[0004] Therefore, in response to the above problems and technical requirements, it is necessary to develop a novel composite electrode structure that integrates efficient spectral conversion function and better environmental stability while maintaining the high performance of silver nanowire electrodes. This would enable a significant improvement in photoelectric conversion efficiency without significantly altering the existing solar cell structure and process, and promote its industrial application. Summary of the Invention
[0005] The purpose of this invention is to provide a flexible transparent electrode with light conversion function, its preparation method and application. It solves the problem that existing transparent electrodes only have a single charge transport function when applied to optoelectronic devices. By using a composite light conversion layer, the traditional transparent electrode is endowed with spectral conversion capability. When applied to optoelectronic devices such as solar cells, the photoelectric conversion efficiency of the device can be effectively improved without changing the original structure of the device.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for fabricating a flexible transparent electrode with photoconversion function includes the following steps: (1) Mix cesium tribromoleadate quantum dot colloidal solution, polymethyl methacrylate, dimethylformamide, and toluene to obtain a photoconversion solution; (2) Spin-coat the silver nanowire solution onto the glass, heat-anneal it, spin-coat polydimethylsiloxane, and cure it to obtain a transparent electrode; (3) Spin-coat the transparent electrode with a light conversion solution, dry it, spin-coat polydimethylsiloxane, cure it, and then peel off the glass to obtain a flexible transparent electrode with light conversion function.
[0007] In this invention, in step (1), the cesium tribromoleadate quantum dot colloidal solution is obtained by mixing cesium tribromoleadate quantum dots with n-hexane. The preparation method of cesium tribromoleadate quantum dots is a conventional method and does not affect the understanding of this invention by those skilled in the art; as an example, cesium tribromoleadate quantum dots are prepared by a conventional hot injection method, with a hot injection reaction temperature of 120~150℃ and a hydrothermal reaction time of 0.5~4.5h.
[0008] In this invention, in step (1), the content of cesium tribromoleadate quantum dot colloidal solution in the photoconversion solution is 14-15%, and the content of polymethyl methacrylate is 7-7.5%.
[0009] In this invention, in step (2), when spin-coating the silver nanowire solution, the rotation speed is 1000~3000 rpm and the time is 25~35s; when spin-coating the polydimethylsiloxane, the rotation speed is 1000~3000 rpm and the time is 25~35s.
[0010] In this invention, in step (2), the temperature of thermal annealing is 100-200℃ and the time is 10-30 min; the temperature of curing is 30-100℃ and the time is 5-20 min.
[0011] In this invention, in step (3), when spin-coating the photoconversion solution, the rotation speed is 1000~3000 rpm and the time is 25~35s; when spin-coating polydimethylsiloxane, the rotation speed is 1000~3000 rpm and the time is 25~35s.
[0012] In this invention, in step (3), the drying temperature is 20-80℃ and the time is 5-20 min; the curing temperature is 30-100℃ and the time is 5-20 min.
[0013] This invention discloses a flexible transparent electrode for photoconversion, comprising a silver nanowire layer, a flexible substrate layer, a photoconversion layer, and an encapsulation layer; the silver nanowire layer, the flexible substrate layer, the photoconversion layer, and the encapsulation layer are stacked sequentially from bottom to top.
[0014] In this invention, the material of the silver nanowire layer is silver nanowire; the material of the flexible substrate layer is polydimethylsiloxane; the material of the light conversion layer includes cesium tribromolead oxide and polymethyl methacrylate; and the material of the encapsulation layer is polydimethylsiloxane.
[0015] This invention discloses the application of the aforementioned flexible transparent electrode for light conversion in the fabrication of flexible optoelectronic devices. Further, the flexible optoelectronic device includes a flexible solar cell and a flexible light-emitting diode.
[0016] Due to the application of the above technical solutions, the beneficial effects of this invention are as follows: This invention creatively introduces a light conversion layer into a transparent electrode, solving the problem that existing transparent electrodes used in optoelectronic devices only have a single charge transport function, endowing traditional transparent electrodes with spectral conversion capabilities, effectively improving the response range of the transparent electrode to the solar spectrum, and in particular enhancing the utilization rate of high-energy photons such as ultraviolet-blue light; furthermore, by introducing a light conversion layer, in conjunction with a flexible substrate layer and an encapsulation layer, the silver nanowire layer is encapsulated and protected, improving the stability of the silver nanowire transparent electrode; the preparation process of this invention is simple, low-cost, and highly practical. When applied to optoelectronic devices such as solar cells, it can significantly improve the photoelectric conversion efficiency of the device without changing the original structure of the device. Attached Figure Description
[0017] Figure 1 This is a schematic diagram illustrating the fabrication method of a flexible transparent electrode with photoconversion function.
[0018] Figure 2 Optical images of the cesium tribromoleadate quantum dot colloidal solution prepared in Example 1 under visible and ultraviolet light.
[0019] Figure 3 The absorption and emission curves of the cesium tribromoleadate quantum dot colloidal solution prepared in Example 1 are shown in the wavelength range of 200-800 nm.
[0020] Figure 4 The absorption and emission curves of the light conversion layer and encapsulation layer prepared in Example 1 in the wavelength range of 200~800nm.
[0021] Figure 5 This is a cross-sectional view of the silver nanowire layer and flexible substrate embedded structure prepared in Example 1.
[0022] Figure 6 Transmittance curves for transparent electrodes (including glass) with different structures.
[0023] Figure 7 Five flexible transparent electrodes with light conversion function were prepared according to the preparation method of Example 1. The sheet resistance of each flexible transparent electrode was taken at 15 different points.
[0024] Figure 8 This is a graph showing the transmittance of commercially available flexible ITO. Detailed Implementation
[0025] The raw materials and molds used in this invention are existing products, and the specific preparation operations and performance testing are conventional techniques. Photoluminescence: The photoluminescence performance of the transparent electrode was tested using an Edinburgh FLS1000 photoluminescence fluorescence spectrometer. Transmittance testing: Measured using a UV spectrophotometer within the wavelength range of 250-800 nm. Sheet resistance testing: The sheet resistance of the transparent electrode was tested using an ST-2258C digital four-probe instrument. Example 1
[0026] A flexible transparent electrode with light conversion function includes a silver nanowire layer, a flexible substrate layer, a light conversion layer, and an encapsulation layer; the silver nanowire layer, the flexible substrate layer, the light conversion layer, and the encapsulation layer are stacked sequentially from bottom to top.
[0027] The silver nanowire layer is made of silver nanowires; the flexible substrate layer is made of polydimethylsiloxane; the light conversion layer is made of cesium tribromolead oxide and polymethyl methacrylate; and the encapsulation layer is made of polydimethylsiloxane.
[0028] A method for fabricating a flexible transparent electrode with photoconversion function includes the following steps: (1) Add 0.814 g of cesium carbonate, 35 ml of octadecene and 0.5 ml of oleic acid to a three-necked flask I. Stir magnetically and heat in an oil bath under a nitrogen atmosphere. React at 120 °C for 1 h and then at 150 °C for 3 h to obtain a dark red cesium oleate precursor solution. (2) Add 0.138 g lead bromide and 10 ml octadecene to a three-necked flask II. Under a nitrogen atmosphere, stir magnetically and heat in an oil bath at 120 °C for 0.5 h. Then add 1 ml oleic acid and 1 ml oleylamine. Add the above cesium oleate precursor solution at 150 °C. Stir magnetically for 5 s. Then cool in an ice-water bath to obtain a mixed solution containing cesium tribromoleadate quantum dots. (3) Transfer the mixed solution containing cesium tribromoleadate quantum dots into a centrifuge tube and centrifuge at 8000 r / min for 4 min; discard the supernatant, add ethyl acetate to the centrifuge tube, place the centrifuge tube in a centrifuge, and centrifuge at 8000 r / min for 4 min; discard the supernatant to obtain a yellow-green solid precipitate, add 6 ml of n-hexane, and sonicate to obtain a homogeneous and clear cesium tribromoleadate quantum dot colloidal solution; (Does the concentration and volume need to be given?) (4) Mix 0.2g of polymethyl methacrylate (Maclin-P821343), cesium tribromoleadate quantum dot colloidal solution, dimethylformamide, and toluene to obtain a photoconversion solution; (5) Place the glass in a surface plasma cleaner for 15 minutes, wherein the power of the surface plasma cleaner is 150W and the pressure is 60Pa; (6) Take a solution of silver nanowires (20 μm long and 30 nm in diameter) (concentration 10 mg / ml, solvent is ethanol) and drop it onto the glass after step (5). Spin coat it at 3000 rpm for 30 s, then anneal it at 150 °C for 15 min, and cool it naturally to obtain a glass / silver nanowire composite layer. (7) Take 5g of Dow Sylgard 184 (existing product) silicone elastomer matrix (component A) and 0.5g of silicone elastomer curing agent (component B) and mix them with magnetic stirring. Then put them into a vacuum drying oven to remove bubbles and obtain polydimethylsiloxane precursor. Drop the polydimethylsiloxane precursor onto silver nanowires and spin coat it at 3000rpm for 30s. Then cure it at 60℃ for 10min. Take it out and cool it to obtain glass / silver nanowire / polydimethylsiloxane composite layer. (8) Take the light conversion solution and drop it onto polydimethylsiloxane. Spin coat it at 3000 rpm for 30 s. Then dry it at 50°C for 10 min under a nitrogen atmosphere to obtain a glass / silver nanowire / polydimethylsiloxane / light conversion composite layer. (9) Take 5g of Dow Sylgard 184 (existing product) silicone elastomer matrix (component A) and 0.5g of silicone elastomer curing agent (component B) and mix them with magnetic stirring. Then put them into a vacuum drying oven to remove bubbles and obtain polydimethylsiloxane precursor. Drop the polydimethylsiloxane precursor onto the light conversion layer and spin coat it at 1000rpm for 30s. Then cure it at 60℃ for 10min. Take it out and cool it to obtain glass / silver nanowire / polydimethylsiloxane / light conversion / polydimethylsiloxane composite structure. (10) The glass is peeled off from the composite structure to obtain a flexible transparent electrode with light conversion function, wherein the thickness of the silver nanowire layer is 0.1 μm, the thickness of the flexible substrate layer is 100 μm, the thickness of the light conversion layer is 0.1 μm, and the thickness of the encapsulation layer is 100 μm.
[0029] Figure 2 Optical images of a cesium tribromoleadate quantum dot colloidal solution under visible and ultraviolet light; from Figure 2 It can be seen that the cesium tribromoleadate quantum dot colloidal solution prepared above exhibits a uniformly dispersed state in aqueous solution, and appears yellowish-green in air and bright green under ultraviolet light.
[0030] Figure 3 The absorption and emission curves of cesium tribromoleadate quantum dot colloidal solution in the wavelength range of 200–800 nm are shown. Figure 3 It is known that cesium tribromoleadate quantum dot colloidal solution has a large absorption in the ultraviolet region (200~360nm) and a low absorption in the visible light region (360~800nm). In addition, cesium tribromoleadate quantum dot colloidal solution has a high intensity emission peak at around 520nm, and there is no overlap between the emission peak and the absorption peak.
[0031] Figure 4 The absorption and emission curves of the light conversion layer and encapsulation layer in the wavelength range of 200~800nm are shown; from Figure 4 It can be seen that the light conversion layer and the encapsulation layer have large absorption in the ultraviolet region (200~360nm) and low absorption in the visible light region (360~800nm). In addition, the light conversion layer and the encapsulation layer have a high intensity emission peak at around 420nm, and there is no overlap between the emission peak and the absorption peak.
[0032] Figure 5 Cross-sectional view of the embedded structure of silver nanowire layers and flexible substrate layer; from Figure 5 It can be seen that the silver nanowires are semi-embedded in polydimethylsiloxane, indicating that there is a high degree of adhesion between the silver nanowires and polydimethylsiloxane. Polydimethylsiloxane can play a certain role in encapsulating the silver nanowires, which helps to maintain the long-term stability of the electrode's electrical performance.
[0033] Figure 6 Transmittance curves for transparent electrodes (including glass) with different structures; from Figure 6 It can be seen that the transmittance of glass + silver nanowires is 89.58%, the transmittance of glass + silver nanowires + polydimethylsiloxane is 86.35%, and the transmittance of glass + silver nanowires + polydimethylsiloxane + light conversion layer + polydimethylsiloxane is 81.8%. This indicates that the introduction of the light conversion layer has little effect on the transmittance of the transparent electrode. However, this invention creatively introduces the light conversion layer into the transparent electrode, enabling the transparent electrode to convert ultraviolet light into visible light, thereby improving the photon utilization rate of optoelectronic devices in the ultraviolet band and significantly improving the photoelectric conversion efficiency.
[0034] Five flexible transparent electrodes with light conversion function were obtained by repeating the preparation method of Example 1. Fifteen different points were taken for each flexible transparent electrode. The sheet resistance test results are shown in [reference]. Figure 7 ;from Figure 7 It can be seen that the sheet resistance of each flexible transparent electrode is relatively stable, basically concentrated in 10-35Ω / sq, and combined with Figure 6 The transmittance indicates that the flexible transparent electrode with light conversion function of the present invention can be fully applied in optoelectronic devices. Comparison Example
[0035] The sheet resistance of currently available flexible ITO is 10Ω / sq, and the transmittance is shown in [reference needed]. Figure 8 This indicates that the optical transmittance performance of the flexible transparent electrode prepared by the present invention is comparable to that of commercially available flexible ITO. Example 2
[0036] A flexible transparent electrode with photoconversion function was prepared according to the preparation method of Example 1, wherein the thickness of the silver nanowire layer is 0.1 μm, the thickness of the flexible substrate layer is 100 μm, the thickness of the photoconversion layer is 0.2 μm, and the thickness of the encapsulation layer is 100 μm. Example 3
[0037] A flexible transparent electrode with photoconversion function was prepared according to the preparation method of Example 1, wherein the thickness of the silver nanowire layer is 0.2 μm, the thickness of the flexible substrate layer is 100 μm, the thickness of the photoconversion layer is 0.1 μm, and the thickness of the encapsulation layer is 100 μm.
[0038] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several modifications and improvements can be made without departing from the principle of the present invention, and these should also be considered to fall within the protection scope of the present invention.
Claims
1. A method for preparing a flexible transparent electrode with photoconversion function, characterized in that, Includes the following steps: (1) Mix cesium tribromoleadate quantum dot colloidal solution, polymethyl methacrylate, dimethylformamide, and toluene to obtain a photoconversion solution; (2) Spin-coat the silver nanowire solution onto the glass, heat-anneal it, spin-coat polydimethylsiloxane, and cure it to obtain a transparent electrode; (3) Spin-coat the transparent electrode with a light conversion solution, dry it, spin-coat polydimethylsiloxane, cure it, and then peel off the glass to obtain a flexible transparent electrode with light conversion function.
2. The method for preparing a flexible transparent electrode with light conversion function according to claim 1, characterized in that: In step (1), the cesium tribromoleadate quantum dot colloidal solution is obtained by mixing cesium tribromoleadate quantum dots with n-hexane.
3. The method for preparing a flexible transparent electrode with light conversion function according to claim 1, characterized in that: In step (1), the content of cesium tribromoleadate quantum dot colloidal solution in the photoconversion solution is 14-15%, and the content of polymethyl methacrylate is 7-7.5%.
4. The method for preparing a flexible transparent electrode with light conversion function according to claim 1, characterized in that: In step (2), when spin-coating the silver nanowire solution, the rotation speed is 1000~3000 rpm and the time is 25~35s; when spin-coating the polydimethylsiloxane, the rotation speed is 1000~3000 rpm and the time is 25~35s.
5. The method for preparing a flexible transparent electrode with light conversion function according to claim 1, characterized in that: In step (2), the temperature of heat annealing is 100-200℃ and the time is 10-30 min; the temperature of curing is 30-100℃ and the time is 5-20 min.
6. The method for preparing a flexible transparent electrode with light conversion function according to claim 1, characterized in that: In step (3), when spin-coating the photoconversion solution, the rotation speed is 1000~3000 rpm and the time is 25~35s; when spin-coating polydimethylsiloxane, the rotation speed is 1000~3000 rpm and the time is 25~35s.
7. The method for preparing a flexible transparent electrode with light conversion function according to claim 1, characterized in that: In step (3), the drying temperature is 20-80℃ and the time is 5-20 min; the curing temperature is 30-100℃ and the time is 5-20 min.
8. A flexible transparent electrode with light conversion function, characterized in that: It includes a silver nanowire layer, a flexible substrate layer, a light conversion layer, and an encapsulation layer; the silver nanowire layer, flexible substrate layer, light conversion layer, and encapsulation layer are stacked sequentially from bottom to top.
9. The flexible transparent electrode with light conversion function according to claim 8, characterized in that: The material of the silver nanowire layer is silver nanowire; the material of the flexible substrate layer is polydimethylsiloxane; the material of the light conversion layer includes cesium tribromolead oxide and polymethyl methacrylate; and the material of the encapsulation layer is polydimethylsiloxane.
10. The application of the flexible transparent electrode with light conversion function as described in claim 8 in the fabrication of flexible optoelectronic devices.